The Relationship Between Stress Levels and The Incidence of Dysmenorrhea in Adolescents - Esti, Amira; Nurhadia, Nurhadia (REAL in Nursing Journal, 2025)
Background: Adolescents can experience dysmenorrhea due to stress exceeding normal limits and inadequate nutrition, which can exacerbate dysmenorrhea. This is because nutritional deficiencies can affect reproductive organ function and increase the risk of menstrual pain in adolescents. This study aims to analyze the relationship between stress levels and the incidence of dysmenorrhea in adolescents. Methods: The study design used an observational analytic approach. The sample of 48 adolescent respondents was selected using a simple random sampling technique using a stress questionnaire (Kessler Psychological Distress Scale) and a dysmenorrhea questionnaire (Numeric Pain Rating Scale). Data were analyzed using the Spearman Rho test (p < 0.05). Results: The results showed a very strong relationship between stress levels and the incidence of dysmenorrhea in adolescents. The p-value of 0.913 (less than 0.05) confirmed the significance of this relationship. Conclusion:  It can be concluded that there is a strong relationship between stress levels and the severity of dysmenorrhea in adolescents in Koto Baru Hiang Village. There is also a significant positive relationship between stress levels and the severity of dysmenorrhea. Adolescents with higher stress levels tend to experience more severe dysmenorrhea. Data also shows that interventions to reduce stress are essential to support adolescent reproductive health and improve their quality of life. Therefore, in-depth education for adolescents is needed to minimize the incidence of stress-related diemesis.